Surgical treatment of hammertoe deformity (a literature review) - D. V. Prozorovskyi (Zaporožskij Medicinskij Žurnal)
Aim. To trace developmental origins of surgical treatment of hammertoe deformity and determine the most commonly used methods of its correction based on the published literature analysis.